Estudo teórico da fotoquímica do clorometano mono-hidratado (CH3Cl:H2O) - Bezerra, Mariana Guedes (2021)
Certain compounds are responsible for the release of radicals directly associated with the unrestrained degradation of atmospheric ozone, among them, can be emphasized chloromethane, being responsible for the emission of 15 to 20% of all of all chlorine present in the catalysis of ozone degradation. Therefore, there is a great interest in understanding the photochemistry of the chloromethane molecule, and it is essential take into account potential molecular interactions between this molecule and other molecules present in large quantities in the atmosphere, such as water molecule. This study seeks to clarify the photochemistry of the monohydrate chloromethane complex, seeking to identify a minimum structure for it, in addition to investigating the electronic and dissociative properties. For this purpose, optimization and single points calculations were performed using multiconfiguration methods (MCSCF and MR-CISD) with aug-cc-pVDZ and d-aug-cc-pVDZ basis functions. In these calculations it was used an active space CAS (10,6) to determine the vertical excitation energies of singlet states. Based on these results, a comparison was made between monohydrate chloromethane complex and chloromethane molecule, confronting the differences between the equivalent states. It was verified that the deviations between the results of the vertical excitation energies of the two compared molecules are between 0.5 to 0.61 eV (MR-CISD). Additionally, it was identified changes in the configurational nature of some equivalent states. In this study, dissociation energies associated with chlorine release channels in the monohydrate chloromethane complex were also characterized. Thus, the ionic state was determined at 4.24 eV above the ground state. The ionic par structure [CH3+(H2O)Cl-] enable to identify two distinct ionic channels, here designated as (a) and (b). These channels differ from each other by the distinct interactions between water molecule and the ions, in channel (a), protonated methanol is formed, while in channel (b), hydrate chloride is formed. Therefore, two different binding energies are determined for the ionic pair, which is bonded to channel (a) by 2.40 eV, while in to channel (b) it is bonded by 4.38 eV. The existence of two distinct neutral channels was also confirmed, thus defining two dissociation energies, these being, respectively, 3.35 eV and 3.25 eV.